CHEMICAL CHARACTERIZATION OF BIOCHAR BRIQUETTES FROM A MIXTURE OF WATER HYACINTH WASTE, CASSAVA PEEL, AND COCONUT SHELLS - Sri Murda Niati; Anjar Siti Mashitoh; Idha Silviyati; Endang Supraptiah; Gemala Cahya; Windi Amanda (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
The use of organic waste such as water hyacinth, cassava peel, and coconut shells can produce high-quality and environmentally friendly biochar briquettes. The manufacturing process includes drying, carbonization, sieving, mixing with tapioca flour as a binder, molding, and final drying. Five variations in composition were systematically tested using a completely randomized design (CRD) method, so that each treatment had the same opportunity and the results were more accurate. The analysis was based on five main chemical parameters: moisture content, ash content, fixed carbon, calorific value, and combustion rate in accordance with the SNI 01-6235-2000 standard. All samples showed acceptable quality, with P1 recording the highest calorific value (6388.21 cal/g), lowest moisture content (5.7%), and most efficient combustion rate (0.095 g/minute). Meanwhile, P2 excelled in having the highest bound carbon content (96.5%), which contributed to a stable and long-lasting flame.